1996
DOI: 10.1063/1.471482
|View full text |Cite
|
Sign up to set email alerts
|

Dipole bound, nucleic acid base anions studied via negative ion photoelectron spectroscopy

Abstract: The anions of the nucleic acid bases, uracil and thymine, were studied by negative ion photoelectron spectroscopy. Both monomer anions exhibit spectroscopic signatures that are indicative of dipole bound excess electrons. The adiabatic electron affinities of these molecules were found to be 93Ϯ7 meV for uracil and 69Ϯ7 meV for thymine. No conventional ͑valence͒ anions of these molecules were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
243
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(265 citation statements)
references
References 44 publications
20
243
1
1
Order By: Relevance
“…The demonstration that dipole-bound anions can serve as precursors to formation of valencelike anions [38][39][40] has generated much interest in their role in electron capture in biological molecules such as uracil and thymine. [41][42][43][44][45][46] In addition, many biologically important molecules can exist as zwitterions, which because of their large dipole moments, can form dipole-bound anions. [46][47][48][49][50] Dipole-bound anions have also been found to be important in charge-transfer processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration that dipole-bound anions can serve as precursors to formation of valencelike anions [38][39][40] has generated much interest in their role in electron capture in biological molecules such as uracil and thymine. [41][42][43][44][45][46] In addition, many biologically important molecules can exist as zwitterions, which because of their large dipole moments, can form dipole-bound anions. [46][47][48][49][50] Dipole-bound anions have also been found to be important in charge-transfer processes.…”
Section: Introductionmentioning
confidence: 99%
“…The important of nonperturbative triples for the dipole bound anions of HCN and HNC has been discussed by Peterson and Gutowski. 32 The realization that CCSD(T) or CCSDT methods together with large flexible basis sets are required to describe accurately dipole bound anions is disconcerting as such calculations are computationally prohibitive for the large molecule or cluster systems currently being studied experimentally and theoretically 42,45,[71][72][73] For these systems, it has often been necessary to compromise on the theoretical method employed.…”
Section: Ab Initio Treatment Of Dipole-bound Anionsmentioning
confidence: 99%
“…There exist two types of radical-anion states of nucleobases: ͑i͒ dipole-bound anions where the excess electron is located far outside the molecule and ͑ii͒ valence ͑co-valently bound͒ anionic state the electron is delocalized over the molecule. The existence of dipole-bound anions was first predicted theoretically by Adamowicz and co-workers 14,15 and subsequently detected in the gas-phase experiments by Desfrançois et al 16 and Hendricks et al 17,18 In the gas phase, the nucleobase anions may be described as electron-dipolebound states. [19][20][21] However, it has been shown that hydrogen bonds between an anion and its surroundings stabilize the valence-bound state.…”
Section: Introductionmentioning
confidence: 99%
“…DBS was predicted to exist for neutral molecules with sufficiently large dipole moments (>2.5D) [130][131][132][133] and had been observed, [134][135][136][137][138] usually with very low binding energies. Excited DBSs near the detachment thresholds of anions were observed by Brauman and co-workers in photodetachment cross sections.…”
Section: A Pes Of Phenoxide At Room Temperature and Observation Of Dmentioning
confidence: 99%